ANALYSIS OF PROGRAM OF BUSINESS CREDIT FOR SOCIETY AT PT BANK BRI - Rasmini, Mas (Departemen Ilmu Administrasi Bisnis, Fakultas Ilmu Sosial dan Ilmu Politik, UNPAD, 2016)
The purpose of this study is to investigate the implementation of a credit program (KUR) in state-owned banks (KUR program of study at Bank Rakyat Indonesia Branch Office Majalaya). The method used is a qualitative method of data collection techniques through in-depth interviews and non-participant observation. Data analysis techniques, namely the reduction of data, display data and then drawing conclusions. While testing is done by triangulation of data and discussions with members of the research team.Results from the study showed that the implementation process of granting KUR fairly and efficiently. That is the process of credit supply is in accordance with the legislation in force, both legislation and circulars BRI. So even in terms of processing time relatively quickly with quite a lot of stages.